Dual Attribution of Conduct to both an International Organisation and a Member State - Stian Øby Johansen (Oslo Law Review)
Responsibility, and in particular attribution of conduct, is one of the most intensely debated issues of public international law in the last couple of decades. In this article I seek to determine whether, how, and when acts or omissions may be attributed both to an international organisation and a member State (dual attribution). My aim is to clarify what dual attribution is, and what it is not. This is done in two steps. First, I (a) define the concept of dual attribution, (b) demonstrate that dual attribution is possible under the current law of international responsibility, and (c) establish a typology of dual attribution. Second, dual attribution is distinguished from three forms of shared responsibility. These are situations of two acts or omissions leading to one injury, derived responsibility, and the notion of piercing the corporate veil of international organisation. I end the article by criticising the disproportionate attention given to dual attribution in legal scholarship, given its limited practical utility.